Volume 1: Plant Operations, Maintenance, Engineering, Modifications and Life Cycle; Component Reliability and Materials Issues; 2009
DOI: 10.1115/icone17-75064
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Informed Safety Margin Characterization

Abstract: The concept of safety margins has served as a fundamental principle in the design and operation of commercial nuclear power plants (NPPs). Defined as the minimum distance between a system's "loading" and its "capacity", plant design and operation is predicated on ensuring an adequate safety margin for safety-significant parameters (e.g., fuel cladding temperature, containment pressure, etc.) is provided over the spectrum of anticipated plant operating, transient and accident conditions. To meet the anticipated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Then feed the X s, j into the function w s , and its output (L ′ s ,C ′ s ) has joint distribution H ′ s . For example, this is exactly the setting of the RISMC studies in Sherry, Gabor, and Hess (2013) and Dube et al (2014), where w s represents a detailed nuclear-specific computer code modeling the progression of a hypothesized accident in a NPP; see Hess et al (2009) for a survey of widely used codes in the nuclear industry. In general, a code run involves numerically solving a system of differential equations, which can require enormous computational effort, making variance reduction crucial to reduce the number of runs needed to achieve an acceptable precision.…”
Section: Stratified Samplingmentioning
confidence: 99%
“…Then feed the X s, j into the function w s , and its output (L ′ s ,C ′ s ) has joint distribution H ′ s . For example, this is exactly the setting of the RISMC studies in Sherry, Gabor, and Hess (2013) and Dube et al (2014), where w s represents a detailed nuclear-specific computer code modeling the progression of a hypothesized accident in a NPP; see Hess et al (2009) for a survey of widely used codes in the nuclear industry. In general, a code run involves numerically solving a system of differential equations, which can require enormous computational effort, making variance reduction crucial to reduce the number of runs needed to achieve an acceptable precision.…”
Section: Stratified Samplingmentioning
confidence: 99%
“…Nuclear engineers employ detailed computer codes (Hess et al 2009) to generate an observation of (L,C), which often entails numerically solving systems of differential equations. We express this through two deterministic functions b L : (0,…”
Section: Mathematical Frameworkmentioning
confidence: 99%
“…Compared to LB-LOCA events, Plant PRAs have indicated that the Small Break LOCA event also can challenge the ability to maintain adequate core cooling. These events typically have a larger impact on CDF and LERF than the LB-LOCA event due to (1) a much higher initiating event frequency, and (2) fewer alternative mechanisms for providing core cooling than for the LB-LOCA case. Small Break LOCA transients are characterized by a gradual top-down draining of the reactor coolant system, with low flow rates in the core relative to those occurring at steady-state or for Large Break LOCA transients.…”
Section: Loca and Beyond Design Basis Eventsmentioning
confidence: 99%
“…The basic concept associated with margins is shown schematically in Figure 1 [2]. In its most simplistic form, the margin is represented as a distance between the load that an SSC experiences (L) and the capacity (C) that the SSC is capable of withstanding.…”
Section: Introductionmentioning
confidence: 99%